Strong resonance effect in a lossy medium-based optical cavity for angle robust spectrum filters - Lee, Kyu-Tae (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.